TYPOLOGY OF GROUNDNUT PODS AND HAULMS PRODUCERS IN THE SUDANESE ZONE OF BENIN - Ahounou, Gbênangnon Serge; DAHOUDA, Mahamadou; Djenontin, Jonas André; AGBOKOUNOU, ARISTIDE MAHOUTIN; Moutouama, Victor; MENSAH, Guy A.; KOUTINHOUIN, G. BENOÎT; HORNICK, Jean-Luc; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2016)
Producers’ typology is a key factor to identify the diversity of existing farms in order to establish development actions. This study aimed to characterize existing groundnut production systems in Northern Benin. Therefore, 126 groundnut farmers were enrolled and interviewed in Borgou and Alibori Departments where by three types of production were identified. In the type 1 (about 42.06% of the study population), most of farmers are not educated and practice mainly agro-breeding and crop production. They do not use much herbicide and practice narrow ploughed ridges using daba (hoe). The production of groundnut haulms is least developed in this system. Majority of farmers found under the type 2 are basically non-educated or in some extents a few had primary or secondary education. This type includes livestock keepers, agro-breeders, agriculturists and traders. They represent 30.26% of the investigated population and almost half of the muse herbicides. For this case, fields are ploughed using farm carts and groundnut haulms production is a well-developed activity. Then comes the type 3 in which most of farmers have at least primary and secondary education. Such farmers are few (27.78%) in the investigated population and are mostly agrobreeders and traders. Cultivation is carried out with carts but also with tractors. Flat ploughed fields are common and herbicides are highly used in this type of production. Most of farmers in this system produce groundnut haulms. The characterization of the three types of producers is used to propose integrated development actions.
Keywords: Typology –Farmers - North – Benin.